Water splitting of hydrogen chemisorbed in graphene oxide dynamically evolves into a graphane lattice. (November 2019) - Ciammaruchi, Laura; Bellucci, Luca; Castillo, Gabriel Comerón; Sánchez, Guillermo Martínez- Denegri; Liu, Quan; Tozzini, Valentina; Martorell, Jordi
Abstract: Graphane offers a safe and high capacity hydrogen storage. Unfortunately, production of graphane directly from its parent material graphene requires breaking the extended π bond, implying either harsh chemical environments or highly energetic plasmas. In here, we propose to use graphene oxide (GO) to initially have the lattice irregularities and local curvature conferring to some of the carbons a favorable partial negative charge or a sp3 hybridization suitable for C–H bond formation. When GO covers the cathode of a water splitting cell powered at 1.7 V, we demonstrate an effective hydrogen chemisorption exhibiting a logarithmic growth with time. Such GO undergoes a dynamic evolution, combining a continuous change in the local corrugation and partial charge distribution with deoxygenation, opening additional sites for hydrogen chemisorption. Using density functional theory combined with the experimental parameters we can monitor the H atom gravimetric density increase as the water splitting experiment takes place. Graphical abstract: Image 1